Effect of benomyl and diazinon on acquired azole resistance in Aspergillus flavus and expression of mdr1 and cyp51c genes - maryam akbari dana; Seyed Jamal Hashemi; roshanak Daei Ghazvini; Sadegh Khodavesi; mona modiri; ladan nazemi; sima darabian; sasan rezaie (Mazandaran University of Medical Sciences, 2019)
Background and Purpose: Aspergillus flavus is an important pathogen in immunodeficient patients. Due to the abundance of this fungus in nature, fungicides are commonly used to preserve and maintain agricultural products. Long-term exposure to these pesticides can lead to the induction of drug resistance in this fungus. Materials and Methods: For the purpose of the study, 10 strains of A. flavus ATCC 204304 were cultured in benomyl and diazinon pesticides at the concentrations of 62.5, 125, 250.500, 750, 1000, 1500, 2000, and 2500 mg/L in nine steps. Morphological changes and resistance to voriconazole, itraconazole, and amphotericin B were evaluated at the end of each step. Subsequently, changes in the expression of mdr1 and cyp51C genes were studied in the strains showing drug resistance. Results: The results showed that during the nine stages of the adjacency of strains with benomyl and diazinon at different concentrations, resistance to voriconazole, itraconazole, and amphotericin B in these toxins increased by 30% and 10%, respectively. In addition, the microscopic examination of resistant strains revealed the absence of sporulation, and only mycelium was found. Macroscopically, the color of the colonies changed from green to white. Furthermore, the investigation of the expression of mdr1 and cyp51c genes in these strains showed a decrease and increase in adjacency with diazinon and benomyl, respectively. Conclusion: As the findings indicated, exposure to agricultural pesticides can lead to the incidence of morphological changes and resistance to amphotericin B, itraconazole, and voriconazole in the sensitive species of A. flavus by altering the expression of genes involved in drug resistance.